Concentration-independent unburnt carbon content metering in fly ash using a waveguide. (November 2019) - Ren, Dantong; Niu, Yuguang; Luo, Huanhuan; Peng, Fan; Gai, Xinhua
Highlights: A method to construct the concentration-independent expression is proposed. The method eliminates the influence of fly ash concentration on measurement accuracy. Calibration equation can predict carbon content independent of concentration change. The experimental results verify the effectiveness of the method. Abstract: This paper presents a high-precision measurement based on microwave to detect unburnt carbon (UC) content. The key idea of the approach is to use two parameters (S21 amplitude and phase) to establish a concentration-independent expression to eliminate the influence of the fly ash (FA) concentration. Compared with single parameter method, the value of concentration-independent expression changes slightly when the FA concentration change, which permits UC content prediction independent of FA concentration. Finally, the proposed method is applied to detect static fly ash samples, and the UC content calibration equation is obtained by fitting the test data. Results of UC content prediction corrected by calibration equation are shown at 12.4, 15.2 and 18 GHz, which indicate that the described method owns high accuracy and is completely independent of concentration fluctuations. Therefore, the concentration-independent expression is a simple and practical method to suppress the concentration fluctuations and improve measurement accuracy.